H-bond plays key role in the synthesis of stable hemiaminals. Issue 15 (12th April 2017) - Islam, Md.; Razzak, Md.; Karim, Mohammad; Mirza, Aminul H.
Graphical abstract: Highlights: Four new hemiaminals have been synthesized. Hemiaminals were formed in polar aprotic solvents. H-bonding was found to play a key in the stability of hemiaminals. Phenanthroline produced intramolecular H-bonding. Dipyridylaldehydes showed intermolecular H-bonding. Abstract: Four new hemiaminals have been synthesized from phenanthroline dialdehyde and di-pyridylaldehydes with 4-amino-3, 5-dimethyl-1, 2, 4-triazole (Fig. 1). Various spectroscopic methods have been used to determine the structures. The effect of solvents and reactant concentrations on these hemiaminals formation have been studied. Stability of these hemiaminals have also been studied both in solution in DMSO and in solid form. Hemiaminal3 was more stable in DMSO than hemiaminal5, 8 and11 . But in solid form, all of these hemiaminals are similarly stable. The results indicated that hydrogen bonding plays a key role on the formation and stabilization of these hemiaminals.